Petani dan Politik: Studi Preferensi Politik Petani Ijen Bondowoso - Rony Zamzam Firdaus; Hary Yuswadi; Raudlatul Jannah (Universitas Trunojoyo Madura, 2019)
This study aims to explain about political preferences and the peasant community, especially in the Curah Macan, Kalianyar Village, Ijen District, Bondowoso Regency East Java. Most of them are Horticulture farmers who use Plantation and Perhutani land. Ijen’s Farmers are often produced cabbage and potatoes. When these two crops have been harvested, it sold to the market, eaten for daily necessities, and there are also some crops that are dried in the sun and reprocessed into new seeds. This research focuses on the peasant and politics which included political affiliation and land tenure in the countryside. The historical impact of land tenure on citizens has an effect on rural political change. Land tenure and subsequent policies such as land leasing, marketing, distribution of plant seeds are related to the political system that occurs in the bulk Macan hamlet and the political life of the community. For this reason, the study uses Robert W. Hefner’s theory of Tengger. It explains farmers and rural politics. The research method is qualitative research methods.